(untitled) (Penerbit UTHM, 2025)
Computational Fluid Dynamics (CFD) has become an indispensable tool in modern mechanical engineering, enabling detailed analysis of fluid flow, heat transfer, and thermal performance across a wide range of systems. This series continues to highlight the diverse studies contributed by researchers from different parts of the world, including distinguished authors from Nigeria and Indonesia, reflecting the global scope and collaboration in CFD. The topics covered include the thermal analysis and temperature distribution in an earth pipe air heat exchanger, the heat transfer behaviour in an infant warmer, and the exergy analysis of a combustor, each emphasising how CFD enhances understanding and design efficiency. Further sections explore the CFD analysis of a shell-and-double concentric tube heat exchanger, heat transfer enhancement in microchannel heat sinks using Mxene-based nanofluids, and the thermal performance evaluation of fuel gas preheaters. Together, these studies illustrate how CFD serves as a powerful tool for innovation, optimisation, and sustainable development in heat transfer applications.